From cocoons to butterflies: Cross-cultural resilience of the first graduates of an international undergraduate pedagogy program at the University of Pécs - Dezső , Renáta Anna (Tudásmenedzsment, 2023)
The University of Pécs, UP has a long tradition of training international students, and educational sciences related programs have a crucial role within this repertoire. Amongst these programs an undergraduate one, i.e. Pedagogy BA – Intercultural Educational Assistant Specialization was developed, authorized and issued in the middle of the Covid 2019 Pandemic. Due to the international nature of the program both its content and command must meet criteria of current standards, therefore it aims at fulfilling the ethos of the 2030 OECD Learning Compass. The first graduates received their degrees in July 2023, and are heading towards their future careers as educators – but are they armed with competences suggested by the OECD 2030 Learning Compass? Besides outlining the peculiarities of the program, and the ways its designers coped with the struggles of the circumstances of the pandemic years via the author’s (i.e. program manager’s) participative-observational narrative description, a brief interpretation of students’ cross cultural resilience is being introduced based on a survey carried out amongst the first graduates. Their feedback is overall positive regarding the development of their own self-perceived cross cultural resilience. Also, it may be concluded that the newly introduced major could cope with the challenges that occurred during the years of the Pandemic. The practical significance of this report is obvious, as it reflects on relevant lessons that may be learnt by the management of the program and initiators of future programs alike. It also calls attention to the significance of the learner’s role shift that may be attached to the OECD 2030 Learning Compass framework.